Essential oil of Hyptis suaveolens (L.) Poit. from Tanzania: Composition and antifungal activity - Malele, R. S. (2003)
The hydrodistellited essential oil (yield 1.2%) of fresh leaves of wild Hyptis suaveolens (L.) Poit. was analysed by GC and GCMS.Twenty four compounds representing 90.3% of the oil was identified. The main compound of the oil were beta caryophyllene, beta elemene, trans alpha bergamotene, spathulenol and bicyclogermacrene The oil exhibit significant antimicrobial activity against Mucor sp. when compared to ketoconazole.